Anti-IL5 and anti-IL5Rα therapy for clinically significant bronchiectasis with eosinophilic endotype: a case series. Issue 1 (23rd January 2020) - Rademacher, Jessica; Konwert, Stefanie; Fuge, Jan; Dettmer, Sabine; Welte, Tobias; Ringshausen, Felix C.
Bronchiectasis is a chronic and often progressive disease, which frequently is associated with significant symptom burden, requiring intensive treatment. Regardless of the multiple potential underlying aetiologies, the vicious cycle of airway inflammation, structural airway damage, impaired mucus clearance and airway pathogen acquisition is the crucial pathogenic pathway for the progression of disease [1]. Patients with clinically significant bronchiectasis featuring an eosinophilic inflammatory endotype who were treated with add-on mepolizumab or benralizumab showed a significant improvement of FEV1, symptom burden and quality of life http://bit.ly/2AZvBLm